STUDY OF CHEMICAL REACTIVITY FOR CO2 MINERALIZATION POTENTIAL IN VOLCANIC ROCK PLUGS FROM THE SERRA GERAL GROUP - Jeovanini Fucks, William; Tauscheck Zielinski, João Pedro; Carvalho da Silva, Stéphanie; Albuquerque Dos Santos, Erico; Rosales Goncalves Oliveira, Antonio; Costabile de Souza , Pedro; Leitão Waichel, Breno; Jacks M dos Santos, Victor Hugo; Dalla Vecchia, Felipe; Soares de Melo Filho, Leonildes; Maria Nunes Ferreira, Cassiane (Boletim Paranaense de Geociências, 2025)
This study investigates the potential of basalts from the Serra Geral Group for geological CO2 storage, focusing on the geochemical behavior of the rocks under reservoir-like conditions at a depth of 900 m. Massive and brecciated basalt samples were characterized in terms of porosity, permeability, and petrography. Closed-system reactor experiments will be conducted at 50 bar and 40 °C for 24 weeks to simulate fluid-rock interactions. Post-experimental analyses will include SEM-EDS, X-ray microtomography, petrographic descriptions to assess mineralogical alterations, and for the fluid; analysis of pH, electrical conductivity, total alkalinity, and chemical composition (ICP-MS and IC). The goal is to evaluate basalt reactivity and its potential for carbonate mineralization and long-term CO2 sequestration.